Potential Interest in Ornamental Plants in Indonesian Society in the Digital Marketing Era - Rusmiyati, Henny (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2024)
The Covid pandemic caused demand for ornamental plants to increase, but sales declined again when the pandemic subsided. These conditions encourage farmers to become agile learners in product marketing following the changes that occur. Digital marketing is a marketing technique that is currently widely used and in demand by the public. Online marketing makes it easy for ornamental plant farmers to introduce their ornamental plant products. The purpose of this research is to find out the interest of the Indonesian people in ornamental plants which are widely sold online. The research method was carried out by means of an online survey with data sources from respondents. The survey results show that more than 200 respondents aged over 40 years occupy the highest position in the number of respondents. Respondents become a benchmark for the views of the community. Public interest in buying ornamental plants is highest with a price range of Rp. 50.000,- up to Rp. 100,000,-. Criteria for selecting ornamental plants based on colour, shape and price of ornamental plants are highly considered, while the scarcity of ornamental plants is optional for some people and for others it is a big consideration when purchasing ornamental plants. Public Satisfaction Buying ornamental plants online is still in a neutral position, so the quality or service of the seller needs to be improved.